From Local Sand to Functional Silicon: An Integrated Pathway for Producing Photovoltaic-Grade Material from Nigerian Silica Sand - MOHAMMED, Tahiru; MAINA, Muhammad B.; MUHAMMAD, Abba B.; SHUWA, Muhammad (FUDMA Journal of Engineering and Technology, 2026)
Nigeria's significant solar energy potential is constrained by a reliance on imported high-purity silicon, despite abundant indigenous silica sand resources. This study presents a complete, integrated experimental pathway to assess the feasibility of producing photovoltaic-grade silicon from River Alau sand in Borno State. The research encompasses: Comprehensive characterization of raw sand using XRF, XRD, and SEM/EDX; Purification via optimized acid leaching (acid was used to remove impurities) and calcination; Carbothermic reduction at a temperature of 1700◦C was carried out to transform the sample to a metallurgical-grade silicon (MG-Si) and subsequent directional solidification; Evaluation of the electrical and optical properties of the upgraded silicon; and Fabrication and outdoor performance testing of simple solar cells under Maiduguri conditions. The raw sand contained 77.63% SiO₂ with significant impurities (Al₂O₃: 2.10%, K₂O: 6.31%). Purification achieved ≥99.6% SiO₂ purity, reducing key metallic impurities to
Keywords: Silica sand, purification, carbothermic reduction, upgraded metallurgical-grade silicon (UMG-Si), photovoltaic, local content, Nigeria.